The Influence of Village Funds, HDI, GRDP, and Unemployment on Poverty in Sulawesi 2017-2024 Using Panel Data Regression - Ramadhani, Muhammad Reza; Utomo, Agung Priyo (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Poverty in Indonesia remains a significant problem. Generally, rural poverty is higher than urban poverty. Therefore, the government has enacted a village fund policy through. Law Number 6 of 2024 to assist development efforts that can reduce rural poverty. However, despite a decline in national poverty, the poverty rate in Sulawesi has fluctuated. In addition to village funds, other variables influence poverty, such as human development index (HDI), gross regional domestic product (GRDP) per capita, and unemployment rate. The purpose of this study is to determine the effect of village funds, HDI, GRDP per capita, and unemployment on poverty rates in 70 districts in Sulawesi from 2017 to 2024. Data used are sourced from directorate general of fiscal balance (DJPK) for village funds and BPS for other variables. Panel data regression analysis is used to identify variables that influence poverty rates. Based on FEM, it is known that HDI and GRDP per capita have a negative and significant effect on poverty rates in Sulawesi Island. Village funds are insignificant in reducing poverty due to differences in development levels across regions. Therefore, equitable development and incre